Association of IceCube neutrinos with radio sources observed at Owens Valley and Metsahovi Radio Observatories - Hovatta T.; Lindfors E.; Kiehlmann S.; Max-Moerbeck W.; Hodges M.; Liodakis I.; Lähteemäki A.; Pearson T. J.; Readhead A. C. S.; Reeves R. A.; Suutarinen S.; Tammi J.; et al. (EDP SCIENCES S A, 2022)
Context. Identifying the most likely sources for high-energy neutrino emission has been one of the main topics in high-energy astrophysics ever since the first observation of high-energy neutrinos by the IceCube Neutrino Observatory. Active galactic nuclei with relativistic jets, also known as blazars, have been considered to be one of the main candidates because of their ability to accelerate particles to high energies.Aims. We study the connection between radio emission and IceCube neutrino events using data from the Owens Valley Radio Observatory (OVRO) and Metsahovi Radio Observatory blazar monitoring programs.Methods. We identify sources in our radio monitoring sample that are positionally consistent with IceCube high-energy neutrino events. We estimate their mean flux density and variability amplitudes around the neutrino arrival time, and compare these with values from random samples to establish the significance of our results.Results. We find radio source associations within our samples with 15 high-energy neutrino events detected by IceCube. Nearly half of the associated sources are not detected in the gamma-ray energies, but their radio variability properties and Doppler boosting factors are similar to the gamma-ray detected objects in our sample, meaning that they could still be potential neutrino emitters. We find that the number of strongly flaring objects in our statistically complete OVRO samples is unlikely to be a random coincidence (at 2 sigma level).Conclusions. Based on our results, we conclude that although it is clear that not all neutrino events are associated with strong radio flaring blazars, observations of large-amplitude radio flares in a blazar at the same time as a neutrino event are unlikely to be a random coincidence.